Parental Involvement and Students’ Discipline in Public Secondary Schools in the Centre and Littoral Regions of Cameroon - Ngefor Azeh Lucy; Zinkeng Njingwa Martina; Ngemunang Agnes Ngale Lyonga (International Journal of Educational Excellence and Innovation, 2024)
The study was carried out to investigate Parental Involvement and Students’ Discipline in Public Secondary Schools in the Centre and Littoral Regions of Cameroon. The mixed method research design was adopted for the study. The accessible population of the study comprised of principals, guidance counsellors and students in 10 public secondary schools in six-sub-divisions in the Mfoundi Division in the Centre Region and Wourri Division in the Littoral Region of Cameroon. The sample size of the study consisted of 400 teachers, 10 principals and 10 guidance counsellors. The participants were sample using the stratified, purposive, random sampling and convenient sampling techniques. Questionnaire and interview guide were the instruments adopted for the study. Quantitative data was analyzed using descriptive and inferential statistical tools. The descriptive statistical tools used were frequency count, percentages, mean, standard deviation and multiple set while qualitative data derived from interview were analyzed using the thematic analysis approach with the aid of themes and quotation. Statistically, findings showed that there is a significant and positive relationship between parental involvement and students’ discipline (R-value 0.511**, p-value < 0.001). The positive sign of the correlation value denotes that students’ discipline will increase more if parents are adequately involved in discipline issues that concern their children and this was supported with a very high predictive explanatory power of 81.9% (Cox and Snell = 0.819). Based on the findings, it was recommended that; parents work cooperatively with other stakeholders of education to influence the improvement and education of their children. Parents should assist with school work, involve in extracurricular activities and do follow up with teachers concerning their children.